PENGETAHUAN MAHASISWA TERHADAP KEANEKARAGAMAN TUMBUHAN DI LINGKUNGAN KAMPUS - yusti, lutfah dwita kurnia (Maliki Interdisciplinary Journal, 2025)
Knowledge of local and scientific plant names is crucial for understanding biodiversity. However, students’ familiarity with these names is influenced by various factors such as study duration, gender, and ethnicity. This study aims to investigate the impact of these factors on the knowledge of local and scientific plant names among Biology students at, particularly regarding the plants found in the campus environment. The results show that the duration of study positively correlates with knowledge of scientific names, though often limited to the genus level. Gender also affects the types of plants known, with males more familiar with construction materials and females more familiar with medicinal plants. Moreover, ethnicity plays a role in local knowledge of plants, especially medicinal plants, which are influenced by the traditions and customs of each ethnic group. This study suggests the need for a more contextual and inclusive teaching approach to enhance students' understanding of plant biodiversity, integrating both scientific and local knowledge.